2005
DOI: 10.1016/j.femsim.2004.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Similar bifidogenic effects of prebiotic-supplemented partially hydrolyzed infant formula and breastfeeding on infant gut microbiota

Abstract: The aim of the study was to assess the quantitative and qualitative differences of the gut microbiota in infants. We evaluated gut microbiota at the age of 6 months in 32 infants who were either exclusively breast-fed, formula-fed, nursed by a formula supplemented with prebiotics (a mixture of fructo- and galacto-oligosaccharides) or breast-fed by mothers who had been given probiotics. The Bifidobacterium, Bacteroides, Clostridium and Lactobacillus/Enterococcus microbiota were assessed by the fluorescence in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
2
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(95 citation statements)
references
References 30 publications
3
87
2
3
Order By: Relevance
“…This difference stems partly from the difference in the composition of the gut microbiota in these two populations. Breast milk stimulates the development of a bifidobacterium rich microbiome in full-term infants (4). Anaerobes such as Clostridium sp., Bacteroides sp., and facultative anaerobes such as Escherichia sp.…”
mentioning
confidence: 99%
“…This difference stems partly from the difference in the composition of the gut microbiota in these two populations. Breast milk stimulates the development of a bifidobacterium rich microbiome in full-term infants (4). Anaerobes such as Clostridium sp., Bacteroides sp., and facultative anaerobes such as Escherichia sp.…”
mentioning
confidence: 99%
“…The importance of fibre in alleviating constipation is well known (Taylor, 1990). In addition, GOS are reported to have a bifidogenic effect (Ito et al, 1990;Bouhnik et al, 1997;Boehm et al, 2002;Moro et al, 2002;Knol et al, 2005;Rinne et al, 2005), and here they may have altered bowel function through an increase in bifidobacteria and a change in the colonic environment. However, there were some subjects on whom the GOS had no effect; in fact, their constipation even became more severe.…”
Section: Discussionmentioning
confidence: 99%
“…GOS are composed of lactose and galactose units (Zaraté and Ló pezLeiva, 1990), and are found naturally in, for example, human milk (Kunz and Rudloff, 1993;McVeagh and Miller, 1997;Kunz et al, 2000). The prebiotic, bifidogenic effects of GOS or a mixture of GOS and fructo-oligosaccharides on the colonic microbiota have been shown in infants Moro et al, 2002;Knol et al, 2005;Rinne et al, 2005) as well as in adults (Ito et al, 1990;Bouhnik et al, 1997;Gopal et al, 2003), and GOS are therefore considered beneficial to human health. As GOS are fermented in the colon, the bacterial mass increases and this in turn increases faecal bulk and softens stools.…”
Section: Introductionmentioning
confidence: 99%
“…One study in term infants consuming either 4 g/l or 8 g/l of this mixture in the formula indicated a dose-dependent increase in Bifidobacterium, whereas Lactobacillus changed with the same increase at both levels of intake (Moro et al, 2002). A number of studies reported that this prebiotic GOS/FOS mixture is able to induce a microbiota that closely resembles the microbiota of breast-fed infants, at the level of the different species of both Bifidobacterium and Lactobacillus Rinne et al, 2005;Haarman and Knol, 2006). Scholtens et al (2006a) showed that this also happens in older children during weaning, when the mixture was added to solid food.…”
Section: Dietmentioning
confidence: 99%